PENGARUH CITRA MEREK DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT PEMBELIAN SECARA ONLINE - Zakky Zamrudi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
Technological developments are very rapid nowadays and make it easier for people to communicate, which one of them is social network sites. The benefit of this platform is the ease to disseminate information both for commercial and communication purposes. This study aims to determine the interaction between users of instagram as one of the largest of social interaction provider nowadaysparticularly on the brand image and their trust in buying intention. The study involved 99 randomly selected people. The results of this study indicate that there are significant interactions between variables either directly or indirectly.